A novel approach for model-based design of gastric pacemakers. (January 2020) - Wang, Luman; Malik, Avinash; Roop, Partha S.; Cheng, Leo K.; Paskaranandavadivel, Niranchan; Ai, Weiwei
Abstract: Understanding the slow wave propagation patterns of Interstitial Cells of Cajal (ICC) is essential when designing Gastric Electrical Stimulators (GESs) to treat motility disorders. A GES with the ability to both sense and pace, working in closed-loop with the ICC, will enable efficient modulation of Gastrointestinal (GI) dysrhythmias. However, existing GESs targeted at modulating GI dysrhythmias operate in an open-loop and hence their clinical efficacy is uncertain. This paper proposes a novel model-based approach for designing GESs that operate in closed-loop with the GI tract. GES is modelled using Hybrid Input Output Automata (HIOA), a well-known formal model, which is suitable for designing safety-critical systems. A two-dimensional ICC network working in real-time with the GES is developed using the same compositional HIOA framework. The ICC network model is used to simulate normal and diseased action potential propagation patterns akin to those observed during GI dysrhythmias. The efficacy of the proposed GES is then validated by integrating it in closed-loop with the ICC network. Results show that the proposed GES is able to sense the propagation patterns and modulate the dysrhythmic patterns of bradygastria back to its normal state automatically. The proposed design of the GES is flexible enough to treat a variety of diseased dysrhythmic patterns using closed-loop operation. Highlights: Closed-loop GES is necessary for treating GI dysrhythmia. The GES can sense the propagation pattern and modulate bradygastria automatically. The GES is flexible to treat various dysrhythmic patterns. The efficacy of the GES is shown by treating gastroparesis and chronic nausea.